Improvement of Science Attitude Through Scientific Approach in Environmental Science Courses - Desi Nuzul Agnafia; Qurrotul Anfa; Anisa Rizkia (Journal of Biology Learning, 2022)
This study aims to determine the increase in science attitude a scientific approach in environmental science courses. The method used in this research is classroom action (CAR). The subjects of this research are science students in semester 3 of the academic year 2021/2022 with a total of 24 people. This research used qualitative descriptive analysis. Based on the results of classroom action research, it can be seen that the scientific attitude of science education in environmental science courses has increased with the application of a scientific approach. The resulting difference is 5.41% between cycle I and II. Cycle I has an average percentage value of 74.61% and cycle II has an average percentage value of 80.02%. The research carried out can successfully foster scientific attitudes in students so that they are successful in learning